Dynamic Control of Neurotransmitter Release by Presynaptic Potential - Zbili, Mickael; Rama, Sylvain; Debanne, Dominique (Frontiers in Cellular Neuroscience, 2016)
Action potentials in the mammalian brain are thought to represent the smallest unit of information transmitted by neurons to their postsynaptic targets. According to this view, neuronal signaling is all-or-none or digital. Increasing evidence suggests, however, that subthreshold changes in presynaptic membrane potential before triggering the spike also determines spike-evoked release of neurotransmitter. We discuss here how analog changes in presynaptic voltage may regulate spike-evoked release of neurotransmitter through the modulation of biophysical state of voltage-gated potassium, calcium and sodium channels in the presynaptic compartment. The contribution of this regulation has been greatly underestimated and we discuss the impact for information processing in neuronal circuits.